An approach to energy conservation in lighting systems using luminaire-based sensor for automatic dimming - Chaiyan Jettanasen; Surakit Thongsuk; Chayanut Sottiyaphai; Panapong Songsukthawan; Pathomthat Chiradeja; Praikanok Lertwanitrot; Santipont Ananwattanaporn; Atthapol Ngaopitakkul (Scientific Reports)
Abstract Lighting systems account for a significant proportion of energy consumption in buildings. Therefore, energy conservation within these systems can greatly enhance overall building energy efficiency. This study proposes a control strategy for LED lamps by adjusting lighting intensity and improving the performance of electric luminaires. The approach involves implementing an automated dimming system that adapts lighting intensity based on surrounding light levels. A system comprising an ambient light sensor, microcontroller, power supply module, dimming controller, and lamp was developed. The sensors measure brightness within a specified range in real time, and the microcontroller analyzes and compares this data against the brightness settings for specific areas. The designed control system was tested in a laboratory setup to demonstrate its effectiveness in a controlled environment. Results showed a 75.65% reduction in power consumption compared to standard lamps in a simulated environment, highlighting its potential for significant energy savings in buildings and its contribution to environmental sustainability.